Serum Iron, Ferritin, Erythroferrone and their Inter-Correlation In Adult Cigarette Smokers: A Case-Control study - Mustafa, Akam Jasim; Jalil, Parwin Jalal; Ade, Jabbar Hamad; Mustafa, Anjam Jasim (Iraqi Journal of Science, 2023)
Cigarette smoking is one of the leading causes of lung and blood cancers worldwide. A higher risk of pulmonary injury is associated with elevated lung iron and ferritin levels. Erythroferrone (ERFE) is a newly discovered tumor necrosis factor (TNF) superfamily member produced by erythroblasts during erythropoiesis. Eventually, it suppresses hepcidin during enhanced erythropoietic activity. The current study investigated the relationship between serum ferritin, iron, and erythroferrone concentrations among adult smokers. This study included 76 selected adult cigarette smokers and 48 healthy individuals (non-smokers) as a control group. The enzyme-linked immunosorbent assay (ELISA) and chemiluminescent immunoassay (CLIA) biochemical techniques were used to accurately measure serum iron, ferritin, and erythroferrone. Cigarette smokers (CS) had a mean age of 42.75±2.92 years, while healthy control (HC) subjects had a mean age of 37.36±2.7 years. The findings have shown a significant increase in serum iron, ferritin, and EREF levels in CS (119± 4.30, 131.1±6.58, and 75.02±2.09) compared with HC (98.67±7.84, 85.50±4.12, and 65.74±2.25) respectively. This study has shown a significant positive correlation between serum EREF (P=0.0072, r=0.4089) and the duration of smoking <20 years and a moderate association between serum iron (P=0.1907, r=0.4511) and the duration of smoking <40 years. For the first time, this outcome shows increased serum EREF and overexpression by erythroblasts in subjects associated with smoking habits, along with increased serum iron and ferritin levels. An indicative correlation is found between EREF overexpression, iron overload, and hyperferritinemia with reference to the duration of smoking. The study also illustrates the interconnection between iron metabolism perturbations and ERFE overexpression induced by cigarette smoking.